Prognostic Characteristics of Immune-Related Genes and the Related Regulatory Axis in Patients With Stage N+M0 Breast Cancer - Tian, Chonglin; Wang, Yongsheng; Song, Xianrang (Frontiers in Oncology, 2022)
Breast cancer (BRCA) incidence has jumped to the top of female tumours. The function of the immune system affects treatment efficacy and prognosis in patients with BRCA. However, the exact role of immune-related genes (IRGs) in stage N+M0 BRCA is unknown. We constructed a predictive risk scoring model with five IRGs (CDH1, FGFR3, INHBA, S100B, and SCG2), based on the clinical, mutation, and RNA sequencing data of individuals with stage N+M0 BRCA sourced from The Cancer Genome Atlas. Results of the Shandong Cancer Hospital and Institute validation cohort suggested that regardless of clinical staging, tumour size, or the number of lymph node metastases, this model was able to reliably discriminate low risk patients from high risk ones and assess the prognosis of patients with stage N+M0 BRCA. Compared with high risk patients, low risk ones can benefit more from immunotherapy. In addition, significant inter-group variations in immunocyte infiltration and the tumour microenvironment were observed. Moreover, risk score and age were found to be independent factors in multivariate COX regression analysis, which influenced the outcome of patients with stage N+M0 BRCA. Based on the above findings, we plotted a prognostic nomogram. Finally, we constructed a lncRNA KCNQ1OT1-LINC00665-TUG1/miR-9-5p/CDH1 regulatory axis of the ceRNA network to explore the mechanism of BRCA progression. To sum it up, we conducted a systemic and extensive bioinformatics investigation and established an IRG-based prognostic scoring model. Finally, we constructed a ceRNA regulatory axis that might play a significant role in BRCA development. More research is required to confirm this result. Scoring system-based patient grouping can help more effectively predict the outcome of patients with stage N+M0 BRCA and determine their sensitivity to immunotherapies, which will aid the development of personalized therapeutic strategies and inspire the research and development of novel medications.